Efficiency vs. Inefficiency in Operations Management: The Singapore Armed Forces (SAF) vs. the Malaysian Armed Forces (MAF) in Southeast Asia?* - Rappa, Antonio L. (BOHR International Journal of Advances in Management Research, 2022)
Why is the Singapore Armed Forces (SAF) considered as highly efficient by foreign experts from Europe, the Middle East, Russia, and China, whereas the Malaysian Armed Forces (MAF), its larger and former neighbor, considered as significantly inefficient? What is it about the SAF that makes it vastly more well-organized and competent as compared to its northern neighbor in terms of the MAF? Are there specific reasons for these wide differences between the two states? This paper analyses the vagaries involved in military operations’ management in training and peacetime as well as during war and overseas deployments.